Agarwood leaf ethanol extract provides neuroprotective properties and promotes cholinergic differentiation of HT22 hippocampal neurons - Kishoree K. Kumaree; James M. Brimson; Kanika Verma; Siriporn Chuchawankul; Tewin Tencomnao; Anchalee Prasansuklab (Scientific Reports)
Abstract Neurodegenerative diseases, characterized by the loss or damage of neurons, represent a growing global health concern. Plants are a rich source of naturally occurring compounds with immense therapeutic potential. Among them, Aquilaria crassna (commonly known as agarwood) is a precious fragrant plant extensively used in cosmetics, perfumes, and traditional Asian medicine. However, its neuroprotective role, particularly in neuroregeneration, has been minimally explored. This study aimed to investigate the therapeutic potential of agarwood leaves in promoting neuroregeneration, with a focus on cholinergic function and neural differentiation. To identify bioactive compounds, a comprehensive LC–MS analysis was conducted on agarwood ethanolic extract (AWE). The phytochemicals detected were further evaluated using in silico methods to predict their interaction with receptor proteins linked to neurodegenerative diseases. Virtual screening revealed that several compounds in AWE exhibited strong binding affinities to receptors such as sigma-1, TrkB, Nogo-66, and p75NTR, providing insights into the potential mechanisms underlying its neuroprotective effects. The in-silico findings were validated through in vitro experiments using HT-22 mouse hippocampal cells as a model. AWE treatment led to a dose-dependent increase in the expression of marker proteins associated with neural differentiation and regeneration, including neuronal nuclei (NeuN), growth-associated protein 43 (GAP43), synaptophysin (Syn), brain-derived neurotrophic factor (BDNF), and the sigma-1 receptor. Additionally, AWE enhanced the expression of specific markers for cholinergic neurons, demonstrating its influence on neuronal development and synaptic function. These findings provide compelling evidence of AWE’s neuroprotective properties, highlighting its potential as a therapeutic agent for neurodegenerative diseases.